Recyclable amberlyst-70 as a catalyst for biginelli reaction: an efficient one-pot green protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones - Chandak, Hemant S.; Lad, Nitin P.; Upare, Pravin P. (Catalysis Letters, 2009)
An environmentally benign aqueous protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones using Amberlyst-70 as a recyclable catalyst has been developed. The use of resinous, nontoxic, thermally stable and inexpensive Amberlyst-70, as a recyclable heterogeneous catalyst, makes the process simple with negligible chemical waste. Thus renders this method an environmentally acceptable synthetic tool for Biginelli reaction.
Keywords: Amberlyst-70; Biginelli reaction; green chemistry; heterogeneous catalysis

Aromatic bromination of aldehydes and ketones using 1,3-di-n-butylimidazolium tribromide [BBIm]Br3 ionic liquids under solvent-free conditions - Borikar, Sanjay P.; Daniel, Thomas (Journal of the Iranian Chemical Society, 2011)
An environmentally benign and efficient process for the preparation of monobromo derivatives of aryl aldehydes and ketones was developed by simple and practical reactions of aryl aldehydes or ketones with 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3), as a brominating reagent under solvent-free conditions in very high yields. The process has several advantages: high conversions, short reaction time, mild reaction conditions, simple workup with good to quantitative yields and re-usable ionic liquid.
Keywords: Bromination; green chemistry; Ionic liquid; Solvent-free; [BBIm]Br-3

Topochemical click reaction: spontaneous self-stitching of a monosaccharide to linear oligomers through lattice-controlled azide-alkyne cycloaddition - Pathigoolla, Atchutarao; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2012)
Keywords: Click chemistry; green chemistry; polymerization; pseudosugars; topochemistry

Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions

Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Synthesis of non-toxic triethyl citrate plasticizer by esterification of renewable citric acid using modified zeolite - Nandiwale, Kakasaheb Y.; Borikar, Sanjay P.; Bokade, Vijay V. (Clean-Soil Air Water, 2015)
Triethyl citrate (TEC), a non-toxic plasticizer, was synthesized by esterification of renewable citric acid (CA, from entire waste of oranges) with ethanol over modified H-ZSM-5 (HZ-5) zeolite. Different micro-meso composites (M-HZ-5) with varying crystallinities were prepared by alkaline treatment of HZ-5. M-HZ-5(0.6) (87% crystallinity) was observed to be a potential and environmentally benign catalyst with 96% CA conversion, 64% TEC selectivity (61.44% TEC yield), and a reusability of six cycles. The probable catalytic mechanism of esterification was also proposed.
Keywords: Biowaste; Catalysts; green chemistry; Micro-mesopre composites; reusability

Problem solving and environmentally benign approach toward diversity oriented synthesis of novel 2-amino-3-phenyl (or Alkyl) sulfonyl-4H-chromenes at ambient temperature - Pandit, Kapil S.; Kupwade, Ravindra V.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (ACS Sustainable Chemistry & Engineering, 2016)
A problem solving, environmentally benign, and diversity oriented protocol has been described for multi component synthesis of medicinally privileged 2-amino-3-phenyl (or methyl) sulfonyl-4H-chromenes by one-pot, three component condensation among aldehydes, phenyl (or methyl) sulphonyl acetonitrile, and alpha-naphthol, 3-dimethylamino phenol, 4-hydroxy-N-methyl-quinoline-2-one as well as 4-hydroxycarbazole, using diethylamine as an efficient organo catalyst. The catalyst employed is commercially available, inexpensive, and nontoxic. Ambient reaction conditions, very high yields, wide scope, and avoidance of conventional isolation as well as chromatographic purification have improved the practical utility of this protocol manifold.
Keywords: 2-Amino-3-methylsulfonyl-4H-chromenes; 2-Amino-3-phenylsulfonyl-4H-chromenes; diethylamine; green chemistry; Multicomponent synthesis; organocatalyst

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane

Ultrasound assisted synthesis of 4-(Benzyloxy)-N-(3-chloro-2-(substitutedphenyl)-4-oxoazetidin-1-yl) benzamide as challenging anti-tubercular scaffold - Nimbalkar, Urja D.; Seijas, Julio A.; Borkute, Rachna; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Sarkar, Dhiman; Nikalje, Anna Pratima G. (Molecules, 2018)
A series of ten novel derivatives of 4-(benzyloxy)-N-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl) benzamide 6a-j were synthesized in good yield from the key compound 4-(benzyloxy)-N-(substituted benzylidene) benzo hydrazide, called Schiff `s bases 5a-j, by Staudinger reaction ([2 + 2] ketene-imine cycloaddition reaction) with chloro acetyl chloride in the presence of catalyst tri ethylamine and solvent dimethyl formamide (DMF), by using ultra-sonication as one of the green chemistry tools. All the synthesised compounds were evaluated for in vitro anti-tubercular activity against Mycobacterium tuberculosis (MTB) and most of them showed promising activity with an IC50 value of less than 1 mu g/mL. To establish the safety, all the synthesized compounds were further tested for cytotoxicity against the human cancer cell line HeLa and all 6a-j compounds were found to be non-cytotoxic in nature. The molecular docking study was carried out with essential enzyme InhA (FabI/ENR) of Mycobacterium responsible for cell wall synthesis which suggests that 6a and 6e are the most active derivatives of the series. The theoretical evaluation of cell permeability based on Lipinski's rule of five has helped to rationalize the biological results and hence the synthesized azetidinone derivatives 6a-j were also analyzed for physicochemical evaluation that is, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties and the results showed that all the derivatives could comply with essential features required for a potential lead in the anti-tubercular drug discovery process.
Keywords: ADMET study; anti-tubercular screening; azetidinone; cytotoxicity study; green chemistry; Molecular docking; ultra-sonication

Bentonite - Clay - supported cuprous iodide nanoparticles (BENT- CuI NPs): a new heterogeneous catalyst in diversity - oriented synthesis of 1, 2, 3-triazoles in aqueous medium - Chavan, V, Pramod; Charate, Shrinivas P.; Desai, V, Uday; Rode, V, Chandrashekhar; Wadgaonkar, Prakash P. (Chemistryselect, 2019)
Bentonite clay supported cuprous iodide nanoparticles (BENT-CuI NPs) were prepared and demonstrated for the first time as an efficient heterogeneous catalyst in diversity oriented, green synthesis of 1,2,3-triazoles by one-pot, three component reaction between alkyl halides, arylboronic acids, or epoxides with alkynes and sodium azide in aqueous medium. The catalyst was characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Energy Dispersive X-ray Spectroscopy(EDS), Scanning Electron Microscopy (SEM), X-Ray Powder Diffraction (XRD), Transmission Electron Microscopy (TEM) as well as Brunauer-Emmett-Teller (BET) techniques and was found to be reusable for five consecutive runs without significant loss of activity.
Keywords: 1; 2; 3-triazoles; arylboronic acids; click synthesis; epoxides; green chemistry; heterogeneous catalyst

New TBAF complex, highly stable, facile and selective source for nucleophilic fluorination: applications in batch and flow chemistry - Said, Madhukar S.; Khonde, Nilesh S.; Thorat, Meghana N.; Atapalkar, Ranjit S.; Kulkarni, Amol A.; Gajbhiye, Jayant; Dastager, Syed G. (Asian Journal of Organic Chemistry, 2020)
Natural polysaccharides supported tetrabutylammonium fluoride (TBAF) complexes are prepared and found to be highly stable and selective fluoride source for well-renowned nucleophilic (SN2 type) fluorination reactions for the first time. Bacterial cellulose, plant cellulose, pectin, and starch derived TBAF complexes are synthesized, characterized (using SEM, TEM, and NMR techniques) and studied for their stability and reactivity. Heterogeneous bacterial cellulose-TBAF complex (NBu4(Bac-cell-OH)F) 1 was found to be highly stable and non-hygroscopic among all complexes, which gave high yields of fluorinated products in multi-gram scale in shorter reaction time. The primarily developed batch protocol was extended to solid-solid continuous flow reaction using an in-house built screw reactor, which furnished products in a few seconds of residence time (tR=20-25 sec) and excellent yields.
Keywords: Flow synthesis; fluorination; green chemistry; Sustainable Chemistry

Catalytic applications of hydrotalcite and related materials in multi -component reactions: concepts, challenges and future scope - Burange, Anand S.; Gopinath, Chinnakonda S. (Sustainable Chemistry and Pharmacy, 2021)
Hydrotalcites (HTs) are the potential substitute to conventional base catalysts. HTs are useful in efficient syntheses of various heterocycles, such as chromenes, pyrans, pyrazoles, triazoles, using multi-component reactions. This review focuses on the chemistry of HTs and particularly hydrotalcites and related materials in the synthesis of heterocycles. The effects of preparation method and, physico-chemical parameters, such as calcination, molar ratio of metals, role of intercalated ions, surface area, on the catalytic activities are discussed. Along with technical aspects, this review also unlocks various untouched areas in developing sustainable catalyst for syntheses of heterocycles, drugs, etc. for the future.
Keywords: green chemistry; green synthesis; heterocycles; heterogeneous catalysis; hydrotalcite; Metal Oxide

Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Burange, Anand S.; Gadam, Komal G.; Tugaonkar, Prajyot S.; Thakur, Seema D.; Soni, Ravish K.; Khan, Rubej R.; Tai, Mubashira S.; Gopinath, Chinnakonda S. (Environmental Chemistry Letters, 2021)
Xanthene and acridine-based heterocyclic compounds find applications in cancer chemotherapy, biological staining and laser dyes and are known for their antibacterial and anti-tumor properties. Here we review green catalytic routes for the synthesis of 1,8-dioxo-octahydroxanthenes, 1,8-dioxo-decahydroacridines and related heterocyclic molecules with catalysts such as metal oxides, mixed metal oxides, resins, supported organocatalysts, heteropolyacids, carbon-based materials, zeolites, sulfides and ionic liquids. We compare protocols for their catalytic activities, and proposed mechanisms are discussed.
Keywords: green chemistry; heterocycles; heterogeneous catalysis; Metal oxides; nanocatalysis

Highly efficient and reusable polymer supported palladium catalyst for copper free sonogashira reaction in water - Sruthi, Pambingal Rajan; Nimmi, Puthan Purayil; Babu, Sukumaran Santhosh; Anas, Saithalavi (ChemistrySelect, 2022)
Development of a novel, greener and efficient heterogeneous catalytic system for copper free Sonogashira reaction in water is described. This novel catalyst can be easily prepared by a simple method through synthetic modification of nitrile group in Polyacrylonitrile (PAN) using monoethanolamine (MEA) followed by its complexation with palladium chloride (PdCl2). The resulting polymer Pd complex (mPAN-Pd) was characterized by means of Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), Inductively Coupled Mass Spectrometry (ICP-MS) and X-ray Photo Electron Spectroscopy (XPS) analyses. mPAN-Pd was then explored as highly efficient heterogeneous catalyst for Sonogashira coupling reaction under copper and ligand free conditions in water affording the corresponding coupling products up to 97 % isolated yield. Moreover, the catalyst was recovered by simple filtration after the reaction and reused for next 5 cycles with excellent stability and activity. This is the first report on the use of ethanolamine modified PAN Pd (II) complex as an efficient heterogeneous catalyst for a coupling reaction.
Keywords: catalysis; green chemistry; Palladium; Polymer Support; Sonogashira coupling

Perception of glycerol carbonate as green chemical: synthesis and applications - Gade, Swapna M.; Saptal, Vitthal B.; Bhanage, Bhalchandra M. (Catalysis Communications, 2022)
Glycerol carbonate (GC) is a prominent component in industrial practice and has a remarkable potential for the sophisticated applications. While GC has come into prominence due to the perceived overflow of glycerol (GLY) as a coproduct of biodiesel industry, its contemporary and future downstream applications are driving tremendous interest in recent years. This review comprises strategies for glycerol carbonate synthesis, properties and its applications. The conversion of GLY to GC via transesterification has appeared in consensus to be the most promising route. A detailed explanation of the effect of the catalysts and operating conditions on the GC yield to provide an updated understanding of the process are summarized. Future directions for GC production through catalytic transesterification are also discussed.
Keywords: Biodiesel; biofuels; catalysis; Glycerol; Glycerol carbonate; green chemistry; transesterification

Facile and eco-friendly synthesis of Mn2O3 nanoparticles via microwave-assisted glycerol-thermal method - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Gehlot, Bhavika; Kamble, Aditi; Manikandan, Marimuthu; Bhosale, Hritvik; Vaishnav, Vishal; Rathod, Rutik; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Chemical Sciences, 2025)
Microwave-assisted efficient synthesis of nanosized manganese oxide (Mn2O3) is reported using glycerol and manganese acetate. Glycerol in this reported methodology acts as an efficient solvent for this nanomaterial synthesis under microwave radiation. This reported method enables the synthesis of nanosized Mn2O3 without further use of additives, stabilizers, and bases other than glycerol and manganese precursor. Glycerol is a renewable biomaterial derived nonvolatile and nontoxic, safe solvent. It has a high boiling point and dielectric constant, which makes it an ideal solvent for microwave synthesis. The synthesized nanosized Mn2O3 was analyzed by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. We examined the catalytic properties of as-synthesized Mn2O3 for cinnamyl alcohol oxidation to cinnamaldehyde. In this oxidation activity experiment, nanosized Mn2O3 exhibits good conversion and selectivity towards the desired product. We also made an attempt to understand the probable mechanism of nanomaterial formation and found some conclusive evidence to support it. This research methodology is facile, energy efficient, and involves minimum chemicals for synthesis. It makes this reported methodology not only economically attractive but also environmentally friendly, which aligns well with green chemistry principles.
Keywords: Glycerol; green chemistry; Nanosized Mn2O3; nanostructured catalysis